Implementasi Konsep Pengelolaan Sampah Ramah Lingkungan (Green Waste) di Kampus Fakultas Teknik Universitas Hasanuddin Kabupaten - Nur Ismi; Muhammad Yamin Jinca; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Waste management in Engineering Faculty of Hasanuddin University currently adopts the conventional paradigm. This is not in line with the vision of the campus as an eco-campus. One aspect to realize an eco-campus is the management of environmentally friendly and sustainable waste. The aim of this research is to identify existing conditions of waste management in case studies and to provide guidance on the application of environmentally friendly waste management based 3R concept (green waste). This research was conducted from September 2019 to April 2020 (8 months). Data collection methods were literature studies, observations and questionnaires. The analysis techniques used were literature synthesis, scoring analysis, and comparative analysis. The results showed that waste in case studies was in the moderate category with a percentage of 52.2%. The concept directives that can be applied were increasing the types of sorting and compartmenting into 4 types, collecting garbage using disaggregated facilities, procuring 3R TPS in the campus area, and increasing the participation of the academic community through waste sorting from its source.